Anxiety Disorders and Psychosocial Intervention Strategies in Social Work Practice-An Updated Review - Fairaq, Fahad Hasan; Amal Mohammad Aljabri; Mohammed Khalifa AlMarashi; Abdullah Hamed Alahmadi; Ghada Mohammad Alalawi; Safaa Ebraheem Flataa; Walaa Gazi Althagafi; Tahani Soud Jamal; Abdullah Muslim Alazmi; Ali Awad Alazmi; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Anxiety disorders are highly prevalent mental health conditions characterized by excessive fear, anticipatory worry, and physiological hyperarousal. They arise from a complex interplay of biological, psychological, and social factors, often leading to chronic impairment and functional decline. Etiological contributors include genetic vulnerability, maladaptive cognitions, trauma, and medical or substance-related influences. Aim: This review aims to synthesize current knowledge on anxiety disorders and examine psychosocial intervention strategies relevant to social work practice. Methods: A narrative review approach was employed, integrating updated evidence on epidemiology, clinical manifestations, pathophysiology, assessment, and management of anxiety disorders. Emphasis was placed on psychosocial frameworks applicable in multidisciplinary care. Results: Anxiety disorders are the most common psychiatric conditions, with specific phobia and social anxiety disorder showing the highest prevalence. Pathophysiological findings highlight dysregulation in neurotransmitter systems and hyperactivity of the amygdala–prefrontal circuitry. Clinical evaluation requires comprehensive history taking and targeted investigations to distinguish primary anxiety from medical mimics. Effective treatment integrates pharmacotherapy—such as SSRIs, SNRIs, and short term benzodiazepines—and evidence based psychotherapy, particularly cognitive behavioral therapy and exposure based modalities. Social workers play a critical role in psychoeducation, linkage to care, and strengthening patient coping capacities. Conclusion: Anxiety disorders present significant clinical and public health burdens. Multimodal, individualized, and interprofessional approaches enhance outcomes and mitigate long term morbidity. Social work practice remains essential in addressing psychosocial contributors and supporting sustained recovery.